Experimental and numerical investigation on 3D printed PLA sacrificial honeycomb cladding. (September 2019) - Rebelo, H.B.; Lecompte, D.; Cismasiu, C.; Jonet, A.; Belkassem, B.; Maazoun, A.
Highlights: Relative density of honeycomb structures greatly influences their blast response. The crushing velocity depends on mass, impulse and relative density of the core. The sacrificial cladding solutions exhibit promising energy dissipation capabilities. Abstract: The increasing use of improvised explosive devices in terrorist attacks against civil targets has challenged the scientific community to find new strengthening or protective solutions, able to mitigate the effects of the blast loads. As a response to this demand, the present study investigates the nonlinear response of 3D printed PLA honeycomb structures in order to analyse their energy absorption capacity when used as the crushable core of a sacrificial cladding solution. The dynamic response of the proposed sacrificial solution is experimentally obtained by means of an explosive driven shock tube, while the corresponding numerical simulations are performed using the commercial finite element software LS-DYNA. Both the experimental and numerical data are in good agreement and clearly show that, as expected, the dynamic force plateau and the specific energy absorption is directly proportional to the considered relative density, which controls the crushing of the top and bottom layers of the PLA honeycomb and the buckling of its interior cell walls. When compared with other available materials, the analysed sacrificial cladding solutions exhibit promising values of energy dissipation and encourage future research in this area.